Linguistic legitimation strategies employed by members of an Indonesian political party - Rizki Ananda; Nova Sari (Universitas Syiah Kuala, 2021)
This study aimed at exploring legitimation strategies used by two members of the Indonesian Solidarity Party (or Partai Solidaritas Indonesia, abbreviated as PSI) in justifying their party leader’s controversial statement on the abandonment of Sharia Law. To do so, it employed critical discourse analysis (CDA) with Leeuwen’s legitimation strategies (2007, 2008) as its analytical tool. The data were obtained from two separate interviews with PSI members aired on two different Indonesian TV channels. The interviews were transcribed and translated. From this process, a 1.170-word corpus, from which the data were derived, was generated. The findings showed that moral evaluation is the most dominant legitimation strategy, followed by rationalization and authorization. In moral evaluation, abstraction occurs most often, followed by evaluation and analogy. In rationalization, theoretical rationalization is used more often than instrumental rationalization. Finally, in authorization, PSI utilized impersonal authority to reject the Sharia Law by referring to academic studies and legal documents which assess the law as being negative. Meanwhile, expert authority was used to build legitimation by reference to experts who support the negative effects of the law. This study implies the power of language to legitimize a controversial activity by using different linguistics strategies.